Introduction - Antiqueira, Moisés (Romanitas - Revista de Estudos Grecolatinos, 2023)
Introduction to the dossier "Greek and Latin historiography: narratives and usages of the past".
Keywords: Dossier; Historiography; Greeks; Romans; Narratives; Past